COVID-19 admissions: Trying to define the real impact of infection in hospitalized patients - Claudia Solito; María Hernández-García; Noelia Arguedas Casamayor; Alba Pavón Ortiz; Rosa Pino; Laia Alsina; Mariona F. de Sevilla (Elsevier, 2024)
Introduction and objective: Several studies have suggested that the hospitalization rate for COVID-19 in children and adolescents may reflect the prevalence of the infection rather than the severity of the disease. The aim of this study was to describe the clinical features of hospitalised paediatric patients with SARS-CoV-2 infection in order to understand if the infection was the reason for admission. Methods: Retrospective cohort study including patients aged 0-18 years with SARS-CoV-2 infection or multisystem inflammatory syndrome in children (MIS-C) admitted to a tertiary care children's hospital in Spain between 01/01/2020 and 12/31/2021. Results: 228 patients were included, corresponding to 150 cases of COVID-related admission (SARS-CoV-2 infection as main cause of hospitalization) and 78 of non-COVID-related admission (SARS-CoV-2 infection unrelated to the hospitalization).In the group of COVID-related admissions, 58 patients had comorbidities. Forty-nine patients had acute respiratory disease (pneumonia, bronchospasm or bronchiolitis). Multisystem inflammatory syndrome in children was diagnosed in 27 and was significantly more frequent in the first year of the pandemic (wild type virus). Eighty percent of patients with acute respiratory disease needed respiratory support, mostly low-flow oxygen therapy. The severity of the disease was similar in all virus variants. Two patients (both with severe comorbidities) died from COVID-related conditions. Conclusions: In our study, one third of the patients were admitted with SARS-CoV-2 infection but not because of it. Acute respiratory disease was less frequent and had a better prognosis compared to the adult population, while MIS-C was a major cause of morbidity and hospitalization. The fatality rate was extremely low. Resumen: Introducción y objetivo: Varios estudios han sugerido que la tasa de hospitalización por COVID-19 en niños y adolescentes puede reflejar la prevalencia de la infección más que la gravedad de la enfermedad. El objetivo de este estudio fue describir las características clínicas de pacientes pediátricos hospitalizados con infección por SARS-CoV-2, con el fin de comprender si este fue el principal motivo de ingreso. Métodos: Estudio de cohortes retrospectivo que incluyó a pacientes de 0 a 18 años con infección por SARS-CoV-2 o síndrome inflamatorio multisistémico pediátrico vinculado a SARS-CoV-2 (SIM-PedS), ingresados en un hospital infantil de tercer nivel en España entre el 01/01/2020 y el 31/12/2021. Resultados: Se incluyeron 228 pacientes: 150 fueron ingresos causados por COVID (infección por SARS-CoV-2 como principal causa de hospitalización) y 78 fueron ingresos no causados por COVID (infección por SARS-CoV-2 no relacionada con la hospitalización). Entre los ingresos causados por COVID, 58 pacientes tenían comorbilidades. 49 pacientes cursaron con enfermedad respiratoria aguda (neumonía, broncoespasmo o bronquiolitis). 27 pacientes fueron diagnosticados de SIM-PedS; este diagnóstico se observó con más frecuencia durante el primer año de la pandemia (variante wild type). El 80% de los pacientes con enfermedad respiratoria aguda necesitaron algún tipo de soporte respiratorio, principalmente oxígeno de bajo flujo. La gravedad de la enfermedad fue similar con todas las variantes del virus. Dos pacientes (ambos con comorbilidades graves) fallecieron por afecciones relacionadas con la COVID-19. Conclusiones: En nuestro estudio, un tercio de los pacientes fueron hospitalizados con infección por SARS-CoV-2 pero no a causa de ella. La enfermedad respiratoria aguda tuvo menos incidencia y mejor pronóstico que en la población adulta, mientras que el SIM-PedS fue una causa importante de morbilidad y hospitalización. La mortalidad fue extremadamente baja.